Policy dialogue as a collaborative tool for multistakeholder health governance: a scoping study. (17th April 2020) - Robert, Emilie; Rajan, Dheepa; Koch, Kira; Muggleworth Weaver, Alyssa; Porignon, Denis; Ridde, Valery
Abstract : Introduction: Health system governance is the cornerstone of performant, equitable and sustainable health systems aiming towards universal health coverage. Global health actors have increasingly been using policy dialogue (PD) as a governance tool to engage with both state and non-state stakeholders. Despite attempts to frame PD practices, it remains a catch-all term for both health systems professionals and researchers. Method: We conducted a scoping study on PD. We identified 25 articles published in English between 1985 and 2017 and 10 grey literature publications. The analysis was guided by the following questions: (1) How do the authors define PD? (2) What do we learn about PD practices and implementation factors? (3) What are the specificities of PD in low-income and middle-income countries? Results: The analysis highlighted three definitions of policy dialogue: a knowledge exchange and translation platform, a mode of governance and an instrument for negotiating international development aid. Success factors include the participants' continued and sustained engagement throughout all the relevant stages, their ability to make a constructive contribution to the discussions while being truly representative of their organisation and their high interest and stake in the subject. Prerequisites to ensuring that participants remained engaged were a clear process, a shared understanding of the goals at all levels of the PD and a PD approach consistent with the PD objective. In the context of development aid, the main challenges lie in the balance of power between stakeholders, the organisational or technical capacity of recipient country stakeholders to drive or contribute effectively to the PD processes and the increasingly technocratic nature of PD. Conclusion: PD requires a high level of collaborative governance expertise and needs constant, although not necessarily high, financial support. These conditions are crucial to make it a real driver of health system reform in countries' paths towards universal health coverage.